Matemática do Céu, Matemática da Terra e Matemática do Sapiens - Charlot, Bernard; Beserra Cavalcanti, José Dilson; Silva, Veleida Anahí da (2022)
Is the teaching of mathematics an ideological and political issue too, despite the representation of mathematics as a set of abstract ideas? The mathematical object is an instrument in social life and, often, it functions as an implicit argument, in a rhetorical use serving an ideological and political project. The article defends the thesis that the key issue is the relationship with Mathematics, which has ideological, political and identity implications. He analyzes three types of relationships: with the Mathematics of Heaven, with the Mathematics of the Earth and with the Mathematics of Sapiens. "Doing mathematics" can be accessing a world of pure Ideas, discovering the deep structures of the world or, as this article maintains, participating in a collective activity of human beings, throughout its history. Mathematical activity is a particular way of appropriating the world, of creating specific symbolic worlds and assuming oneself as a subject of knowledge, a singular subject and a member of a species called Sapiens. Therefore, obviously, Mathematics is always, at the same time, a scientific, social and anthropological activity.
Será que o ensino da Matemática é também um assunto ideológico e político, apesar da representação da Matemática como conjunto de ideias abstratas? O objeto matemático é instrumento na vida social e, muitas vezes, ele funciona como argumento implícito, em um uso retórico a serviço de um projeto ideológico e político. O artigo defende a tese de que a questão chave é a da relação com a Matemática, que tem implicações ideológicas, políticas e identitárias. Ele analisa três tipos de relações: com a Matemática do Céu, com a Matemática da Terra e com a Matemática do Sapiens. "Fazer matemática" pode ser aceder a um mundo de Ideias puras, descobrir as estruturas profundas do mundo ou, como se sustenta neste artigo, participar de uma atividade coletiva dos seres humanos, no decorrer da sua história. A atividade matemática é uma forma particular de se apropriar o mundo, de criar mundos simbólicos específicos e de se assumir como sujeito de saber, sujeito singular e membro de uma espécie chamada Sapiens. Portanto, obviamente, sempre a matemática é, ao mesmo tempo, uma atividade científica, social e antropológica.
Keywords: Mathematics teaching; Relationship with Knowledge; Ideology; Ensino de Matemática^lpt; Relação com o Saber; Ideologia